(3EQTGO GdCPgGfs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3CHh WGdH GdeWHHs)
(3ChdgG (B:s
(3GdMeO ddg GdeJaQO HGdbOe hGdOhGe(B... (3hHYO aEf Gddg JYGdi ceG ChLH Ydi GdhdO WGYI CHhjg cPdc ChLH YdjgeG GdTabI Ydjg(B...s
(3BNQgG (B:s
(3heY JYOO GdLfGjGJ JYOO GdOjGJ(B... (3agPG NdGUI(B... (3hef CQGO GdJWhjd HPcQ GdaQhY (B... (3aYdjg HcJGHfG GdeSei(B: (3efJgi GdeWdH(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B284s
(3GdCYdGe(B: (3L(B2(3, (B227s
(3GdCYdGe(B: (3L(B2(3, (B227s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B284s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis